Clinical Predictors of Facial Nerve Outcomes After Surgical Resection of Vestibular Schwannoma. (May 2021) - Ren, Yin; MacDonald, Bridget V.; Tawfik, Kareem O.; Schwartz, Marc S.; Friedman, Rick A.
Objective: To identify clinical predictors of facial nerve (FN) outcomes after microsurgical resection of vestibular schwannoma (VS). Study Design: Prospective cohort study. Setting: Academic medical center. Methods: Consecutive patients undergoing VS resection from November 2017 to October 2019 were included. FN function was evaluated with the House-Brackmann (HB) scale and stratified into good (HB I-II) and poor (HB III-VI) function. Analyses included descriptive statistics, correlation, and logistic regression. Results: Of 256 patients who met criteria (mean age, 47.7 years; 62.5% female), 227 (88.7%) achieved good FN function postoperatively and 238 (93.0%) at latest follow-up (mean, 154.8 days). Operative approaches consisted of translabyrinthine (50.8%), retrosigmoid (25.0%), and middle fossa craniotomies (24.2%). Extent of resection was decided intraoperatively, and gross or near total resection was accomplished in 237 (92.6%) cases. Postoperative HB grade correlated with latest HB grade (0.615, P < .001). Factors associated with good postoperative FN function included small tumor size (≤15 mm; odds ratio [OR], 2.425; P = .042), gross or near total resection (OR, 3.170; P = .041), and ≥100-µV intraoperative FN electromyographic response to a 0.05-mA stimulus (OR, 22.242; P < .001). Factors associated with good FN function at latest follow-up included gross total resection (OR, 7.764; P = .003) and ≥100-µV FN electromyographic response (OR, 8.518; P < .001), accounting for surgical approach and tumor size. Conclusion: Microsurgical resection of VS can be accomplished with excellent FN outcomes. Gross total resection and ≥100-µV intraoperative FN electromyographic response predicted excellent FN outcomes. Immediate postoperative FN function is a prognosticator of long-term FN function.